Tissue-resident immune cells in homeostasis and tissue repair - A. P. Toptygina (Медицинская иммунология)
Most types of immune cells are able to freely enter tissues, perform surveillance functions, and then leave them, while distinct cells are permanently located in non-lymphoid tissues. Such cells comprise tissue-resident populations (TR). Non-lymphoid tissues are home to a diverse community of innate and innate-like immune cells, such as tissue-resident macrophages (TRMφ), innate lymphocytes (ILC), γδT cells, NKT cells, MAIT cells, B1 cells, and marginal zone B cells. Previously, TR cells were thought to be derived from hematopoietic stem cells, but most TR cells are shown to be derived from erythromyeloid precursors of the yolk sac and fetal liver. TR cells have some features of “stemness”, they have the ability to self-renew, like classical hematopoietic stem cells. TR cells live in tissues due to trophic factors produced within these tissues, thus maintaining homeostasis at their microenvironment. Homeostatic factors for TRMφ are interleukin 34 (IL-34), monocyte and granulocyte-monocyte colony-stimulating factors; for ILC, γδT cells; for NKT and MAIT cells, IL-7 and IL-15; for B1 cells, IL-5. The concept of only 4 types of tissues (epithelial, connective, nervous and muscular) seems to be outdated, a more appropriate paradigm suggests existence of minimal tissue modules. In this case, each module consists of cell elements that interact with each other much more strongly than with elements outside the module. Cell associations within tissue modules provide homeostatic support to other cells that make up the module, being a niche for these cells, thus providing niche support for the former elements. Moreover, TR cells represent the first line of immune defense, since the vast majority of pathogens penetrate the body through barrier tissues. Repopulation of TR cells, that die in response to infection occurs by proliferation of the remaining TR cells, and due to migration of bone marrow-derived cells into the tissues. There are competitive relationships between these two repopulation pathways. At the same time, bone marrowderived TR cells are not capable of self-renewal and cannot fully reproduce all the functions of classical TR cells. TR cells ensure the removal of cellular debris and dead cells, regulate inflammation, remodel the extracellular matrix and produce tissue growth factors.